Controversies and Transformations in Digital Zakat Fundraising: Trends, Urgencies, and Solutions Within the Framework of Maqasid As-Syariah - Imam Agung Prakoso; Mustafid (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The digital transformation of zakat fundraising represents a pivotal shift in Islamic philanthropy, aiming to enhance efficiency, transparency, and accessibility. However, the integration of digital systems with the normative framework of Maqasid al-Shariah remains underexplored. This study investigates the controversies, transformations, and challenges in digital zakat fundraising through a qualitative phenomenological approach, involving 25 informants across four zakat institutions in Kalimantan, Indonesia. The findings reveal that while digital platforms such as e-wallets, mobile apps, and QRIS have improved financial traceability and user convenience, the alignment with Maqasid al-Shariah principles is partial. The study identifies three core dimensions: (1) Hifz al-Mal (wealth protection), evident in enhanced accountability and reduced financial leakage; (2) Hifz al-Din wa al-Ijtima’i (religious and social preservation), supported by digital religious education and productive zakat programs; and (3) al-‘Adalah (social justice), which remains challenged by digital access disparities and uneven zakat distribution. Despite improvements, the current digital zakat ecosystem tends to favor urban beneficiaries, leaving rural communities underserved. The study advocates for a Maqasid-based digital governance framework to ensure ethical, inclusive, and sustainable zakat distribution. These insights contribute to the theoretical advancement of Islamic financial technology and offer strategic implications for policymakers, zakat institutions, and sharia-compliant innovation designers.